Hemin, a heme oxygenase-1 inducer, restores the attenuated cardioprotective effect of ischemic preconditioning in isolated diabetic rat heart. (August 2017) - Gupta, I; Goyal, A; Singh, NK; Yadav, HN; Sharma, PL
Background: Attenuated cardioprotective effect of ischemic preconditioning (IPC) by reduced nitric oxide (NO) is a hallmark during diabetes mellitus (DM). Recently, we reported that the formation of caveolin–endothelial nitric oxide synthase (eNOS) complex decreases the release of NO, which is responsible for attenuation of IPC-induced cardioprotection in DM rat heart. Heme oxygenase-1 (HO-1) facilitates release of NO by disrupting caveolin–eNOS complex. The activity of HO-1 is decreased during DM. This study was designed to investigate the role of hemin (HO-1 inducer) in attenuated cardioprotective effect of IPC in isolated diabetic rat heart. Methods: DM was induced in male Wistar rat by single dose of streptozotocin. Cardioprotective effect was assessed in terms of myocardial infarct size and release of lactate dehydrogenase and creatine kinase in coronary effluent. The release of NO was estimated indirectly by measuring the release of nitrite in coronary effluent. Perfusion of sodium nitrite, a precursor of NO, was used as a positive control. Result: IPC-induced cardioprotection and increased release of nitrite were significantly attenuated in a diabetic rat as compared to a normal rat. Pretreatment with hemin and daidzein, a caveolin inhibitor, alone or in combination significantly restored the attenuated cardioprotection and increased the release of nitrite in diabetic rat heart. Zinc protoporphyrin, a HO-1 inhibitor, significantly abolished the observed cardioprotection and decreased the release of nitrite in hemin pretreated DM rat heart. Conclusion: Thus, it is suggested that hemin restores the attenuated cardioprotective effect in diabetic rat heart by increasing the activity of HO-1 and subsequently release of NO.